Analysis of Xamarin capabilities for building mobile multi-platform applications - Dras, Michał; Fila, Grzegorz; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2018)
The article presents Xamarin platform which is used to create cross-platform application for Android, iOS, MacOS and Universal Windows Platform. This article shows Xamarin platform and a test application that has been used to investigate platform’s capabilities and effectiveness in creating multi-platform applications. Inspections prove that Xamarin allows to create multi-platform applications in a more effective way without losing too much on performance of these applications on individual platforms and systems.